2021
DOI: 10.3389/fcell.2021.689028
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Subtype-Specific Molecular Characteristics of Breast Cancer by Multiomics Analysis of Prognosis-Associated Genes, Driver Genes, Signaling Pathways, and Immune Activity

Abstract: Breast cancer is a heterogeneous malignant disease with different prognoses and has been divided into four molecular subtypes. It is believed that molecular events occurring in breast stem/progenitor cells contribute to the carcinogenesis and development of different breast cancer subtypes. However, these subtype-specific molecular characteristics are largely unknown. In this study, we employed 1217 breast cancer samples from The Cancer Genome Atlas (TCGA) database for a multiomics analysis of the molecular ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…Our study also disclosed that the Basel, LumB, and HER2 subtypes accounted for larger proportions in the high-risk group than the low-risk group; meanwhile, the LumA subtype showed the opposite trend. Furthermore, Li et al reported that an altered CDH1 group involving mutations in the LumA subtype group displayed better survival than a non-altered group (56). This could explain our current result, indicating that a higher CDH1 mutation rate in the low-risk group is associated with better prognosis in comparison to the high-risk group.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our study also disclosed that the Basel, LumB, and HER2 subtypes accounted for larger proportions in the high-risk group than the low-risk group; meanwhile, the LumA subtype showed the opposite trend. Furthermore, Li et al reported that an altered CDH1 group involving mutations in the LumA subtype group displayed better survival than a non-altered group (56). This could explain our current result, indicating that a higher CDH1 mutation rate in the low-risk group is associated with better prognosis in comparison to the high-risk group.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, Li et al. reported that an altered CDH1 group involving mutations in the LumA subtype group displayed better survival than a non-altered group ( 56 ). This could explain our current result, indicating that a higher CDH1 mutation rate in the low-risk group is associated with better prognosis in comparison to the high-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…ERα, together with other transcription factors such as FoxA1, TFAP2C, and GATA3 are key factors in the determination and maintenance of the epithelial phenotype of mammary cells, as activated not only by estrogen, but also by other signaling pathways [ 9 , 10 ]. This activity is reflected in BC, since tumors that retain the expression of ERα show several epithelial features and, clinically, are less invasive and aggressive than other subtypes exhibiting mesenchymal features [ 11 ]. The transcriptional activity of ERα in breast tumor cells has been the subject of an impressive number of research papers in the last decades, especially because it represents one of the prototypes of druggable molecules in cancer, testified by the success of Tamoxifen and other antiestrogens in BC treatment since 1975 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This cancer is primarily classified according to the histopathological characteristics (approximately 95% are ductal or lobular carcinomas) and secondarily according to the hormone receptors and other cellular markers. Based on the expression of the estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), and the proliferative index Ki-67, breast cancer can be classified into different molecular subtypes: luminal A (ER-positive, PR-positive, HER2-negative, Ki-67 with less than 20%); luminal B HER2-negative (ER-positive, HER2-negative, and either PR-low or Ki-67 with more than 20%); luminal B HER-2-positive (ER-positive or PR-positive, HER2-positive or amplified, and any Ki-67); HER2-enriched (ER-negative, PR-negative, HER2-positive or amplified, and any Ki-67); and triple-negative (ER-negative, PR-negative, and HER2-negative) breast cancer [ 24 , 25 , 26 ]. It is worth mentioning that the ER has two different isoforms ERα and ERβ, which have contradictory functions on the proliferative activity of the breast [ 27 ].…”
Section: Introductionmentioning
confidence: 99%